Impact of the COVID-19 Pandemic on ST-Elevation Myocardial Infarction Management in Hunan Province, China: A Multi-Center Observational Study - Tang, Liang; Wang, Zhao-jun; Hu, Xin-qun; Fang, Zhen-fei; Zheng, Zhao-fen; Zeng, Jian-ping; Jiang, Lu-ping; Ouyang, Fan; Liu, Chang-hui; Zeng, Gao-feng; Guo, Yong-hong; Zhou, Sheng-hua (Frontiers in Cardiovascular Medicine, 2022)
Background This study aimed to investigate the impact of the COVID-19 pandemic on ST-segment elevation myocardial infarction (STEMI) care in China. Methods We conducted a multicenter, retrospective cohort study in Hunan province (adjacent to the epidemic center), China. Consecutive patients presenting with STEMI within 12 h of symptom onset and receiving primary percutaneous coronary intervention, pharmaco-invasive strategy and only thrombolytic treatment, were enrolled from January 23, 2020 to April 8, 2020 (COVID-19 era group). The same data were also collected for the equivalent period of 2019 (pre-COVID-19 era group). Results A total of 610 patients with STEMI (COVID-19 era group n = 286, pre-COVID-19 era group n = 324) were included. There was a decline in the number of STEMI admissions by 10.5% and STEMI-related PCI procedures by 12.7% in 2020 compared with the equivalent period of 2019. The key time intervals including time from symptom onset to first medical contact, symptom onset to door, door-to-balloon, symptom onset to balloon and symptom onset to thrombolysis showed no significant difference between these two groups. There were no significant differences for in-hospital death and major adverse cardiovascular events between these two groups. Conclusion During the COVID-19 pandemic outbreak in China, we observed a decline in the number of STEMI admissions and STEMI-related PCI procedures. However, the key quality indicators of STEMI care were not significantly affected. Restructuring health services during the COVID-19 pandemic has not significantly adversely influenced the in-hospital outcomes.